2022
DOI: 10.1111/jre.12978
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of human gingival fibroblasts by Th1‐, Th2‐, Th17‐, and Treg‐derived cytokines

Abstract: Background and objective The purpose of this study was to evaluate whether gingival fibroblasts (GFs) can be differently activated and polarized into distinct functional subtypes by T‐helper (Th) cytokines. Methods Gingival fibroblasts were stimulated with interferon (IFN)‐γ, interleukin (IL)‐4, IL‐17, and transforming growth factor (TGF)‐β, representative cytokines of Th1, Th2, Th17, and regulatory T cells, respectively, and the gene expression profiles were analyzed by microarray. Differentially expressed ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, the involvement of nuclear factor–κB (NF-κB) and mitogen-activated protein (MAP) kinases in this process has been thoroughly characterized (Båge et al 2010). Interestingly, the cytokines interferon-γ (IFN-γ) and IL-4 skew polarized GFs into functionally distinct subtypes that differ in their potential to activate immune cells and effect tissue repair (Ha et al 2022), as well as their responses to oral pathogens (Jang et al 2021). Although these in vitro phenotypes represent the extremes of the polarization spectrum and are unlikely to exist in vivo, single-cell analysis of the healthy oral mucosa identified transcriptionally distinct subtypes of oral fibroblasts that are characterized by gene signatures associated either with inflammatory responses or with collagen synthesis and matrix remodeling (Williams et al 2021).…”
Section: Modulation Of Gf Activation By the Environment Of The Oral M...mentioning
confidence: 99%
“…Furthermore, the involvement of nuclear factor–κB (NF-κB) and mitogen-activated protein (MAP) kinases in this process has been thoroughly characterized (Båge et al 2010). Interestingly, the cytokines interferon-γ (IFN-γ) and IL-4 skew polarized GFs into functionally distinct subtypes that differ in their potential to activate immune cells and effect tissue repair (Ha et al 2022), as well as their responses to oral pathogens (Jang et al 2021). Although these in vitro phenotypes represent the extremes of the polarization spectrum and are unlikely to exist in vivo, single-cell analysis of the healthy oral mucosa identified transcriptionally distinct subtypes of oral fibroblasts that are characterized by gene signatures associated either with inflammatory responses or with collagen synthesis and matrix remodeling (Williams et al 2021).…”
Section: Modulation Of Gf Activation By the Environment Of The Oral M...mentioning
confidence: 99%
“…DCs play a crucial role in the priming and differentiation of CD4+ T cells into several distinct subsets, including Th1, Th2, and Th17, as well as regulatory T cells (Treg) ( 33 ). Categorization of Th cells is usually based on a dominant cytokine or even a family of cytokines, including Th1 (IL-6, INF-γ, TNF-α), Th2 (IL-4, IL-5, IL-6, IL-10, IL-13), Th17 (IL-17, IL-21, IL-22), and Treg (TGF-β, IL-10, IL-35) ( 34 ) ( Figure 4A ). Here, we monitored the dominant cytokine levels to determine the Th polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic analysis and preclinical studies have confirmed C3 as a potential pharmacological target for periodontitis treatment (Alayash et al, 2023; Hajishengallis et al, 2021). gingival fibroblasts stimulated with IFN-γ (GF(IFN-γ)) up-regulated the expression of chemokines (CXCL9, -10, -11, CCL8), molecules involved in antigen presentation, complement component 3 (C3), and other immune response-related molecules (Ha et al, 2022). Our experimental results have demonstrated that CD81+ gingival fibroblasts are an important source of C3.…”
Section: Discussionmentioning
confidence: 99%